Pengaruh Terapi Self-Compassion Pada Ansietas Saat PJJ (Pembelajaran Jarak Jauh) Di SMK Bunga Persada Cianjur Tahun 2021: The Effect of Self-Compassion Therapy on Anxiety During PJJ (Distance Learning) at Bunga Persada Vocational School Cianjur in 2021 - Devi Septiani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Distance Learning Methods. In foreign terms, it is called distance learning. In various other studies also known as online learning, e-learning, and online. The enactment of Distance Learning during the COVID-19 pandemic, caused some students to experience. Anxiety or anxiety is a sense of worry that arises because it feels that something unpleasant will happen. Anxiety at some level is considered normal, but if there is continuous anxiety where homeostasis function fails to adapt, there will be pathological anxiety.             Methods: This research uses this type of quantitative research. This study uses a pre-experimental design with a pre-post test design in one group and one group pre-post design. The feature of this study is to reveal a causal relationship by involving one group of subjects. The group of subjects was observed before intervening and then observed again after the intervention. With the technique of giving Self-Compassion therapy, then given a watershed questionnaire.   Results: Statistical test results using the Wilcoxon test. The results of significant assessments of the overall test from Asym. sig in the output table of test statistics. The p-value in asym-sig is obtained at 0,004 < 0,05. This means that there is an effect on the level of anxiety before the intervention and after the intervention with measurements for two measurements of Self-Compassion therapy to the level of anxiety. It can be concluded that the research data has the effect of Self-Compassion therapy on anxiety levels during distance learning at Bunga Persada Vocational School Cianjur in 2021. Discussion: The conclusion is that there is an effect of giving Self-Compassion therapy on anxiety during distance learning at Bunga Persada Vocational School Cianjur in 2021.